Initiating Constitutional Morality: Political Intervention, Ethical Reinforcement, and Constitutional Court Decisions in Indonesia - Annisa Salsabila; Tria Noviantika; Ahmad Yani (Constitutional Review, 2024)
Constitutional morality is essential for the branches of power (Parliament and Government) to ensure impartiality, political insularity, and institutional stability for the judicial power, especially the Constitutional Court and constitutional morality as a guide and benchmark for constitutional judges to form ethics and decisions that reflect the Constitution. This article seeks to answer crucial questions about how forms of intervention and ethical problems in the Constitutional Court do not reflect constitutional morality and how the idea of limiting intervention and strengthening the ethics and decisions of the Constitutional Court through constitutional morality. The author uses normative legal research methods with statutory, conceptual, comparative, and case approaches. The results of this study are in line with the hypothesis of the argumentation that the author builds, showing that the lack of application of constitutional morality by Parliament, Government, and Constitutional Court Judges has threatened the independence of the Constitutional Court, has damaged the judicial dignity of the Constitutional Court, and making the Constitutional Court a means of political insurance. Several cases have shown that parliamentary and government intervention in the Constitutional Court is inevitable. Likewise, ethical violations and decisions of the Constitutional Court that do not reflect the Constitution add to the complexity of the current problems of the Constitutional Court. For this reason, the author recommends that the elaboration of the concept of limiting intervention and strengthening the ethics and decisions of the Constitutional Court can be accomplished in several ways, including statutory provisions regarding the prohibition of conflicts of interest and the ethics of state administrators, the construction of ethical institutions/courts as external institutions in enforcing and supervising ethics, reconstructing the process of selecting and dismissing constitutional judges fairly and transparently by involving public oversight, and guaranteeing and legitimizing the Constitutional Court in exercising administrative and financial autonomy independently.